Servant leadership and engagement: a dual mediation model. Issue 6 (13th August 2018) - Bao, Yuanjie; Li, Chaoping; Zhao, Hao
Abstract : Purpose: The purpose of this paper is to compare two mediating mechanisms of servant leadership's effect on followers' work engagement: the social exchange mechanism (represented by leader-member exchange (LMX)) and the social learning mechanism (represented by public service motivation in Study 1 and prosocial motivation in Study 2). Design/methodology/approach: In Study 1, the authors collected two-wave matched data from 216 public sector employees. In Study 2, the authors collected two-wave matched data from 178 private sector employees. The authors use hierarchical regression and bootstrapping to test the hypotheses. Findings: Servant leadership is positively related to follower's work engagement and this relationship is mediated by LMX, but not by public service motivation (Study 1) or prosocial motivation (Study 2). It suggests that servant leadership promotes followers' work engagement mostly through the social exchange mechanism. Research limitations/implications: The data were collected from Chinese employees, and future studies are necessary to verify the findings in other cultural contexts. Originality/value: This study sheds light on a more nuanced picture of the effect mechanisms of servant leadership.